PARTISIPASI GENERASI MUDA DALAM REVITALISASI LAPANGAN KELURAHAN MANDAN KECAMATAN SUKOHARJO KABUPATEN SUKOHARJO - Sri Riris Sugiyarti; Suwardi Suwardi; Isnaini Miladiani (Jurnal Abdimas Bina Bangsa, 2022)
Youth is one of the potential aspects in the social order as the continuation of the nation's struggle and a resource for development. The advancement of a country is largely determined by the thoughts and active contributions of the younger generation. One of the steps taken by the younger generation to bring this nation in a better direction is the active participation of youth in community development. The field is a public facility that can create crowds. The younger generation can channel their positive talents, such as sports activities, recreation and economic activities. Revitalization is a process or method and action to revive something that was previously helpless to become empowered, so revitalization means to make something or act vital. The problem that is often encountered in the younger generation is not optimizing participation in the development sector. Socialization activities are expected to be able to add insight and knowledge to the younger generation in participating in field development. The target in this service is youth in the Mandan Village, Sukoharjo District, Sukoharjo Regency. The method used is lecture and question and answer. The result of this activity is that youth gain insight and knowledge about participation in development and have the enthusiasm to be involved in field development activities